Three-dimensional electronic resistivity mapping of solid electrolyte interphase on Si anode materials. (January 2019) - Stetson, Caleb; Yoon, Taeho; Coyle, Jaclyn; Nemeth, William; Young, Matt; Norman, Andrew; Pylypenko, Svitlana; Ban, Chunmei; Jiang, Chun-Sheng; Al-Jassim, Mowafak; Burrell, Anthony
Abstract: Silicon is a promising candidate for the lithium ion battery (LIB) anode because of the order-of-magnitude improvement in capacity over current state-of-the-art graphite anodes. In systems featuring both C and Si anodes, electronic resistivity of the solid-electrolyte interphase (SEI) layer is a critical factor for preventing continuous electrolyte-decomposition reactions at the electrode/electrolyte interface. However, the in-situ measurement of SEI electronic resistance has been complicated by ion transport and electronic contributions from other parts of the battery circuit. Ex-situ measurements of SEI resistivity at microscopic scales are also lacking. We report on a nanometer-resolution three-dimensional technique that enables ex-situ mapping of electronic resistivity of SEI formed on a model single-crystalline wafer Si anode. Our novel experimental approach uses scanning spreading-resistance microscopy resistance imaging and mechanical depth profiling. In addition to resistance mapping, this method also provides an alternative technique for locating buried interfaces, where mechanical or electronic properties differ sufficiently between layers. Further validation of this method was obtained by resistance mapping of a reference sample with a designed α-Si:H layer stack of different doping concentrations. The results show relatively uniform lateral resistivity distribution of the SEIs but steep decreases in resistivity in the vertical direction. Resistivity vs. depth profiles are highly dependent on cycling conditions, but they generally show a resistivity decrease from the most superficial levels of SEI and a thickness increase with continued cycling prior to SEI stabilization. The most prominent resistivity increase was observed on SEI formed in Gen2 electrolyte (EC:EMC [3:7 by wt.] + 1.2 M LiPF6 ) with 10 wt% fluoroethylene carbonate additive; this result may partially explain the significant improvements of sustained electrochemical cycling and coulombic efficiency observed with this electrolyte additive. Our approach provides a novel and unparalleled three-dimensional approach in characterizing electronic resistivity, which contributes significantly to understanding SEI formation and the intrinsic properties critical to battery performance. Graphical abstract: fx1 Highlights: Electronic properties of the SEI formed on Si anodes is mapped in the nanoscale. Electronic resistivity of the SEI decreases steeply from the surface. SEI resistivity and thickness are dependent on cycling conditions and electrolyte. The described technique presents utility in locating buried interfaces.